Practice Bulletin No. 164: Diagnosis and Management of Benign Breast Disorders. Issue 6 (June 2016) - N/A
Abstract : Breast-related symptoms are among the most common reasons women present to obstetrician–gynecologists. Obstetrician–gynecologists are in a favorable position to diagnose benign breast disease in their patients. The purpose of a thorough understanding of benign breast disease is threefold: 1) to alleviate, when possible, symptoms attributable to benign breast disease, 2) to distinguish benign from malignant breast disease, and 3) to identify patients with an increased risk of breast cancer so that increased surveillance or preventive therapy can be initiated. Obstetrician–gynecologists may perform diagnostic procedures when indicated or may make referrals to physicians who specialize in the diagnosis and treatment of breast disease. The purpose of this Practice Bulletin is to outline common benign breast disease symptoms in women who are not pregnant or lactating and discuss appropriate evaluation and management. The obstetrician–gynecologist's role in the screening and management of breast cancer is beyond the scope of this document and is addressed in other publications of the American College of Obstetricians and Gynecologists (1–3 ).